2015
DOI: 10.1111/1742-6723.12475
|View full text |Cite
|
Sign up to set email alerts
|

Public health in Australasian emergency departments: Attitudes, barriers and current practices

Abstract: Objective: To understand the attitudes of consultant emergency medicine physicians and advanced trainees and the perceived barriers to public health interventions in Australasian EDs. Methods:This was a voluntary crosssectional, mixed-methods online survey of consultant emergency physicians and advanced trainees of the ACEM, conducted between December 2011 and March 2012. Results: Eight hundred and fifty-six ACEM members responded to the survey -a response rate of 33%. A similar number of consultants (70%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Studies that utilised existing ‘standard care’ were as likely to show benefit from an ultra‐BI as those with a contrived control group. It is likely that current ‘standard care’ does not routinely include provision of even a pamphlet to at‐risk drinkers . The studies that have used ED clinicians have resulted in a significant loss to follow up in addition to a high rate of refusal .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that utilised existing ‘standard care’ were as likely to show benefit from an ultra‐BI as those with a contrived control group. It is likely that current ‘standard care’ does not routinely include provision of even a pamphlet to at‐risk drinkers . The studies that have used ED clinicians have resulted in a significant loss to follow up in addition to a high rate of refusal .…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, since 2007, it has been mandatory for all level 1 Trauma Centres to offer SBIRT to all patients . A recent survey of Australasian Emergency Physicians indicates broad support for public health and health promotion in ED, impeded by significant barriers including lack of resources and time …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar expectations for public health‐related competencies are found in the American Board and the Royal College of Emergency Medicine curriculums . Moreover, a previous study showed that a majority of Australasian Emergency Physicians and trainees believe that specific public health training is necessary …”
Section: Discussionmentioning
confidence: 99%